4D rods: 3D structures via programmable 1D composite rods. (5th January 2018) - Ding, Zhen; Weeger, Oliver; Qi, H. Jerry; Dunn, Martin L.
Abstract: Slender 1D structures are ubiquitous in nature and engineering and serve as building blocks for 3D structures at scales ranging from molecular to architectural. 3D printing enables fabrication of such structures with geometrical complexity that cannot be produced easily by traditional manufacturing methods, but comes with a cost of long building time and need for supporting structures during printing. Some of these limitations are overcome here through an approach that prints 1D rods with composite cross-sections, programmed to deform into a prescribed 3D shape simply upon heating. The straight or curved composite rods consist of a glassy polymer and an elastomer that are bonded to each other as a result of the manufacturing process; the latter is programmed with a compressive stress during the printing process. When heated, the stiff glassy polymer softens, resulting in release of the stress in the elastomer, and causes the 1D structure to deform into a new permanent 3D configuration. The cross-section of the composite rods can be designed to enable deformation modes of bending and twisting, a combination of which can guide the 1D rod into almost any 3D shape. With the use of a nonlinear thermomechanical computational model, several 3D rod structures are designed and demonstrated, highlighting the potential for increased functionality with material and time savings. Graphical abstract: Highlights: Direct 4D printing of programmable 1D composite rods that can rapidly change into 3D structures is demonstrated. Simulation-based design of 1D composite rods and rod assemblies with printing-induced compressive strains is developed. Complex permanent 3D shapes are achieved through design of the spatial layout of multiple materials in a 1D rod configuration. The 4D printing method saves 70%–90% printing time and printing materials compared with direct printing of 3D structures.